Role of endogenous and exogenous antioxidants in risk of six cancers: evidence from the Mendelian randomization study - Zhu, Jiahao; Lian, Jie; Wang, Xin; Wang, Ren; Pang, Xiangyi; Xu, Benjie; Wang, Xing; Li, Chenyang; Ji, Shengjun; Lu, Haibo (Frontiers in Pharmacology, 2023)
Background: Although oxidative stress is known to contribute to cancer, and endogenous and exogenous antioxidants are thought to prevent tumorigenesis by suppressing oxidative stress-induced DNA damage, antioxidants have also been reported to show negative effects on tumor formation, necessitating characterization of the causal associations between antioxidants and cancer risk. Methods: In this study, Mendelian randomization (MR) analysis, primarily inverse-variance weighted MR, was used to assess the causal effect of six endogenous and five exogenous diet-derived antioxidants on the risk of six cancers. MR-Egger intercept test and Cochran’s Q statistic were utilized to assess pleiotropy and heterogeneity, respectively. Results: For endogenous antioxidants, a bidirectional two-sample MR analysis was conducted. Our findings suggested that serum albumin has a negative causal association with the risk of prostate cancer [odds ratio (OR) = 0.78, 95% confidence interval (CI): 0.68–0.91, p = 0.001]. The risks of the six cancers showed no significant associations with endogenous antioxidants in the converse MR analysis. For exogenous antioxidants, the unidirectional two-sample MR analysis exhibited a nominal relationship between the serum retinol level and non-small-cell lung cancer risk (OR = 0.29, 95% CI: 0.11–0.76, p = 0.011). Conclusions: Thus, our study revealed the protective effects of genetic susceptibility to high circulating albumin levels on prostate cancer, providing potential targeted interventions for prostate cancer prevention.